2007
DOI: 10.1111/j.1742-481x.2006.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial of Hydrofiber dressing with silver versus povidone–iodine gauze in the management of open surgical and traumatic wounds

Abstract: This prospective, randomised clinical trial compared pain, comfort, exudate management, wound healing and safety with Hydrofiber dressing with ionic silver (Hydrofiber Ag dressing) and with povidone-iodine gauze for the treatment of open surgical and traumatic wounds. Patients were treated with Hydrofiber Ag dressing or povidone-iodine gauze for up to 2 weeks. Pain severity was measured with a 10-cm visual analogue scale (VAS). Other parameters were assessed clinically with various scales. Pain VAS scores decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 30 publications
1
58
1
4
Order By: Relevance
“…Moreover, the results were better than that described by other authors [30][31][32]36,37]. This can be explained only by a small amount of our pilot study -certainly in the larger sample and in groups using interactive and vacuum-assisted dressings should be a certain percentage of complications.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…Moreover, the results were better than that described by other authors [30][31][32]36,37]. This can be explained only by a small amount of our pilot study -certainly in the larger sample and in groups using interactive and vacuum-assisted dressings should be a certain percentage of complications.…”
Section: Resultscontrasting
confidence: 53%
“…Also, some authors recommend using interactive dressings based on carboxymethyl cellulose impregnated with silver ions as preventive measures, noting their high clinical efficacy as compared with standard dressings [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Additionally, multiple clinical studies have demonstrated the efficacy of AQUACEL Ag dressing in a variety of chronic and acute wounds. [8][9][10] These studies reported positive clinical outcomes related to control of bacterial balance, wound healing, pain at dressing changes, cost-effectiveness, time to healing, frequency of dressing changes, and nursing time.…”
Section: Peer-reviewed Datamentioning
confidence: 99%
“…More advanced products, like traditional and modern dressings, represent a cost-effective therapy to protect the wound from the external environment and to prevent wound contamination and dehydration [115,150]. Due to their high water absorption rates, adhesion to the wound bed and increased pain during dressing changes, traditional dressings (e.g., gauze, cotton wool) are often employed as secondary dressings to allow the exudate drainage and to support the application of more effective products (e.g., skin substitutes) [77,115]. Traditional dressings have been largely replaced by modern dressings, which are capable of creating and maintaining a moist environment in the wound bed, ideally suited for cellular migration and proliferation [81,115,124,150,151].…”
Section: Therapeutic Options For Skin Reconstructionmentioning
confidence: 99%
“…They are commonly used as cleaning and antimicrobial agents, allowing wound bed preparation and decontamination [8,67]. To extend their efficacy, facilitate their handling and improve their impact on the wound, most of these therapeutic compounds have been embedded within gauzes or incorporated within dressing materials [2,77]. More advanced products, like traditional and modern dressings, represent a cost-effective therapy to protect the wound from the external environment and to prevent wound contamination and dehydration [115,150].…”
Section: Therapeutic Options For Skin Reconstructionmentioning
confidence: 99%